Evaluation of HER2/Neu Receptors and Its Comparison with Pathologic Parameters in Rural Breast Cancer Patients in Eastern India - Wasim, Nazir Abdul; Majumdar, Arijit; Konar, Karabi; Sadhukhan, Prasenjit; Bhattacharjee, Debanjan (Annals of Pathology and Laboratory Medicine, 2024)
Background: The proto-oncogene Her-2/neu (c-erb-B2) has become an increasingly important prognostic and predictive factor in breast cancer. Overexpression/amplification of Her-2/neu has been associated with a worse outcome in patients with breast cancer. Hormone receptor expression has been reported to be low in breast cancer patients from developing countries, including India. The pattern of receptor expression in rural areas is not well studied. Materials and Methods: Immunohistochemistry was used for the evaluation of HER-2/neu expression in the mastectomy specimens. Tumor size from the mastectomy specimen was recorded, and the number of lymph nodes was noted. Tissue processing and staining with hematoxylin and eosin were done. Post-mastectomy grading of the malignant breast lesion was done according to the Scarff-Bloom-Richardson (SBR) grading system in hematoxylin and eosin stained slides. Results: Among the histopathological types of the tumors, IDC NOS constituted 40 cases (86.9%), invasive lobular carcinoma constituted 2 cases (4.3%), medullary carcinoma 2 cases (4.3%), invasive papillary carcinoma and mucinous carcinoma 1 case each (2.2%). The number of HER-2/neu positive cases was 28 (60.9%) and 18 cases were found negative (39.1%). The total number of ER positive and negative cases were 21 (45.7%) and 25 (54.3%), respectively. The total number of PR positive cases was 18 (39.1%) and that of negative cases was 28 (60.9%). Conclusion: HER-2/neu overexpression is significantly associated with clinicopathological parameters such as younger age group, increased tumor size, higher tumor grades, axillary lymph node metastases, skin involvement, and higher clinical staging.